Glycation in Demetalated Superoxide Dismutase 1 Prevents Amyloid Aggregation and Produces Cytotoxic Ages Adducts - Sirangelo, Ivana; Vella, Filomena M.; Irace, Gaetano; Manco, Giuseppe; Iannuzzi, Clara (Frontiers in Molecular Biosciences, 2016)
Superoxide dismutase 1 (SOD1) has been implicated with familial amyotrophic lateral sclerosis (fALS) through accumulation of protein amyloid aggregates in motor neurons of patients. Amyloid aggregates and protein inclusions are a common pathological feature of many neurological disorders in which protein aggregation seems to be directly related to neurotoxicity. Although extensive studies performed on the aggregation process of several amyloidogenic proteins in vitro allowed the identification of many physiological factors involved, the molecular mechanisms underlying the formation of amyloid aggregates in vivo and in pathological conditions are still poorly understood. Post-translational modifications are known to affect protein structure and function and, recently, much attention has been devoted to the role played by non-enzymatic glycation in stimulating amyloid aggregation and cellular toxicity. In particular, glycation seems to have a determining role both in sporadic and familial forms of ALS and SOD1 has been shown to be glycated in vivo. The aim of this study was to investigate the role of glycation on the amyloid aggregation process of both wild-type SOD1 and its ALS-related mutant G93A. To this aim, the glycation kinetics of both native and demetalated SOD have been followed using two different glycating agents, i.e. D-ribose and methylglyoxal. The effect of glycation on the structure and the amyloid aggregation propensity of native and ApoSOD has been also investigated using a combination of biophysical and biochemical techniques. In addition, the effect of SOD glycated species on cellular toxicity and reactive oxygen species (ROS) production has been evaluated in different cellular models. The results provided by this study contribute to clarify the role of glycation in amyloid aggregation and suggest a direct implication of glycation in the pathology of fALS.